ظاهرة التلكؤ الدراسي لدى طلبة المدارس الحكومية في محافظة جنوب الباطنة وعلاقتها بخداع الذات - الباردي, سعود (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت الدراسة إلى التعرف على مستوى شيوع ظاهرة التلكؤ الدراسي ومستوى شيوع خداع الذات لدى طلبة المدارس الحكومية في محافظة جنوب الباطنة، والكشف عن الفروق ذات دلالة إحصائية في مستوى شيوع ظاهرة التلكؤ الدراسي ومستوى شيوع خداع الذات لدى طلبة الصف الحادي عشر في محافظة جنوب الباطنة تعزى لمتغيرات الجنس ونوع الدراسة، واستقصاء العلاقة ذات الدلالة الإحصائية بين مستوى ظاهرة التلكؤ الدراسي ومستوى خداع الذات لدى طلبة المدارس الحكومية في محافظة جنوب الباطنة. تم تطبيق مقياس التلكؤ الدراسي (إعداد الباحث) ومقياس خداع الذات للخصوصي (2018) على (133) طالبا وطالبة بالصف الحادي عشر في محافظة جنوب الباطنة، وأسفرت النتائج عن شيوع ظاهرة التلكؤ الدراسي بدرجة متوسطة، وشيوع ظاهرة خداع الذات بدرجة متوسطة، وعدم وجود فروق ذات دلاله إحصائية في شيوع ظاهرة التلكؤ الدراسي وفقا لمتغيري الجنس ونوع الدراسة، وعدم وجود فروق ذات دلاله إحصائية في مستويات خداع الذات وفقا لمتغير الجنس، بينما وجدت فروق دالة احصائيا عند مستوى دلالة 0.05 في مستويات خداع الذات وفقا لمتغير نوع الدراسة ولصالح البحتة، كما وُجد ارتباط منخفض وطردي دال عند مستوى دلالة 0.01 بين التلكؤ الدراسي وخداع الذات. وقد أوصت الدراسة بالعمل على تنمية الجوانب الإيجابية لدى الطلبة والتي من شأنها ان تحد من خطورة هذا السلوك وتقلل من انتشاره كزيادة الدافعية للإنجاز وتنمية ثقتهم بأنفسهم وإمكانياتهم وقدراتهم، وحثهم على المثابرة والانضباط للوصول لأهدافهم. Abstract: The study aimed to identify the level of prevalence of the phenomenon of scholastic procrastination and the level of the prevalence of self-deception among students of public schools in the Governorate of South Al Batinahin Oman, and to reveal the statistically significant differences in the level of prevalence of the phenomenon of scholastic procrastination and the level of the prevalence of self-deception among students of the eleventh grade in the Governorate of South Al Batinahin Oman due to the variables Gender and type of study, and the investigation of the statistically significant relationship between the level of the phenomenon of scholastic procrastination and the level of self-deception among public school students in the Governorate of South Al Batinah in Oman. The scholastic procrastination scale (prepared by the researcher) and the self-deception scale (Alkhososy, 2018) were applied to (133) eleventh grade students in the Governorate of South Al Batinah in Oman; The results revealed the prevalence of the phenomenon of scholastic procrastination to a medium degree, the prevalence of the phenomenon of self-deception to a medium degree, There are no statistically significant differences in the prevalence of the phenomenon of scholastic procrastination according to the variables of sex and type of study, and there are no statistically significant differences in the levels of self-deception according to the gender variable, while there are statistically significant differences at the level of significance of 0.05 in the levels of self-deception according to the variable of the study type and in pure favor Also, a low and direct significant correlation was found at the 0.01 significance level between scholastic procrastination and selfdeception, The study recommended working on developing the positive aspects of students, which would limit the danger of this behavior and reduce its spread, such as increasing the motivation for achievement, developing their confidence in themselves, their capabilities and abilities, and urging them to persevere and discipline to reach their goals.
مقال
Keywords: التلكؤ الدراسي ; طلبة المدارس الحكومية ; خداع الذات; scholastic procrastination; public school students; Self deception